The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1136/bjsports-2015-094755
|View full text |Cite
|
Sign up to set email alerts
|

Boxing injury epidemiology in the Great Britain team: a 5-year surveillance study of medically diagnosed injury incidence and outcome

Abstract: Injury prevention should aim to protect the hands and wrists of elite amateur boxers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 17 publications
3
41
1
9
Order By: Relevance
“…Other skin diseases were acne, seborrheic dermatitis, burn/scald accidental injury, scabies, fungal infection and palmoplantar keratoderma. The findings are consistent with the study conducted by Masqoor et al [1] and Sarwar et al [5].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other skin diseases were acne, seborrheic dermatitis, burn/scald accidental injury, scabies, fungal infection and palmoplantar keratoderma. The findings are consistent with the study conducted by Masqoor et al [1] and Sarwar et al [5].…”
Section: Discussionsupporting
confidence: 93%
“…More over in this study almost all workers are belong to low socio-economics class, they have limited excess to healthcare, lack of sufficient health education. All these factors produce a cumulative affect to their health which can be prevented by providing improved work place, protective means, health education, adequate health services and improving professional skills [5].…”
Section: Discussionmentioning
confidence: 99%
“…The hand and wrist have previously been identified as locations that have a high risk of injury in amateur boxers 16,33 but not professional boxers. 4 This investigation adds to our current understanding of hand and wrist injury in elite amateur boxers, by demonstrating that carpometacarpal instability and finger metacarpophalangeal joint extensor hood and capsule also known as "boxer's knuckle" injuries were the most common injury diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Injuries during both amateur and professional boxing have been documented in many previous investigations, [2][3][4]16,25,33,35,36 but most attention has been paid to head and neurodegenerative injuries and conditions as a result of boxing. 15 A recent 5-year prospective investigation of injuries in elite amateur boxing showed that injuries to the hand region were in fact the most frequent and also led to the most time lost from training and competition.…”
Section: Introductionmentioning
confidence: 99%
“…These forces are absorbed mainly on the knuckles and travel into the rest of the hand creating injuries at the hand-wrist region. Although the main injuries are ligament us sprains and tears, fractures have also been observed [5]. Management of these injuries using the correct objective criteria, linked to the current available technology is therefore important [2].…”
Section: Introductionmentioning
confidence: 99%